2019
DOI: 10.1186/s40659-019-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reduces store-operated Ca2+ entry and enhances the apoptosis of fibroblast-like synoviocytes in adjuvant arthritis rats model via targeting ORAI1–STIM1 complex

Abstract: Background Resveratrol was reported to trigger the apoptosis of fibroblast-like synoviocytes in adjuvant arthritis rats but the subcellular mechanism remains unclear. Since ER stress, mitochondrial dysfunction and oxidative stress were involved in the effects of resveratrol with imbalance of calcium bio-transmission, store operated calcium entry (SOCE), a novel intracellular calcium regulatory pathway, may also participate in this process. Results In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Emerging evidence indicated that FLSs exhibit abnormal proliferation and insufficient apoptosis, which drives Mediators of Inflammation synovial hyperplasia and inflammatory response in the pathophysiology of RA [3,4]. Current evidence indicated that natural products inhibited the biological behaviors of activated FLSs, which might provide new insights into the treatment of RA [5,17]. The natural polyphenol EA has been reported to have antioxidant, anti-inflammatory, and anticancer biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicated that FLSs exhibit abnormal proliferation and insufficient apoptosis, which drives Mediators of Inflammation synovial hyperplasia and inflammatory response in the pathophysiology of RA [3,4]. Current evidence indicated that natural products inhibited the biological behaviors of activated FLSs, which might provide new insights into the treatment of RA [5,17]. The natural polyphenol EA has been reported to have antioxidant, anti-inflammatory, and anticancer biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggested the influence of calcium channel antagonists on attenuation of drug dependence, addiction and reinstatement of nicotineconditioned (Biala, Budzynska, 2006;Biala, Budzynska, 2008;Padula et al, 2015). The majority of prior research using resveratrol showed it exhibits antagonist effects on calcium channels (Lu et al, 2019;Nalli et al, 2016;Yin et al, 2017). Resveratrol may diminish nicotine-induced CPP by affecting calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 25 mg/kg of this compound can also decrease articular edema, NF-κB, and neutrophil elastase, and hence, diminish neutrophil extracellular traps, in RA rats, namely, by interfering with TLR-4, peptidyl arginine deiminase 4 enzyme and COX-2 [336]. Resveratrol at 45 mg/kg can also reduce store-operated Ca 2+ entry and enhance the apoptosis in an adjuvant arthritis rat model by targeting the ORAI1-STIM1 complex [329]. Additionally, Fernández-Rodríguez et al [330] reported that 12.5 mg/kg/day resveratrol can also induce the noncanonical autophagy pathway, reduce p62 expression, caspase-3 expression, and poly(ADP-ribose) polymerase, IL-1β, C-reactive protein, and prostaglandin E2, as well as NF-κB synovial tissue expression, which is correlated with p62 expression [330].…”
Section: In Vivo Studiesmentioning
confidence: 99%